Red to Near‐Infrared Mechanochromism from Metal‐free Polycrystals: Noncovalent Conformational Locks Facilitating Wide‐Range Redshift. (3rd March 2021) - Zhu, Chenfei; Luo, Qing; Shen, Yunxia; Lv, Chunyan; Zhao, Sanhu; Lv, Xiaojing; Cao, Feng; Wang, Kunyan; Song, Qingbao; Zhang, Cheng; Zhang, Yujian
Abstract: Piezochromic organic materials that present a large difference in fluorescence wavelength in the near‐infrared region have important potential applications; however, few such metal‐free luminophores have been reported. In this study, we design and prepare π‐conjugated electron acceptors whose planar conformation can be locked by the noncovalent interactions. The planar fused‐ring geometry can narrow the optical band gap, enhance the molecular stability and rigidity, as well as increase the radiative rate. As expected, the polymorphs Re‐phase and Ni‐phase emit the high‐brightness fluorescence with wavelength maxima ( λ em, max ) at 615 and 727 nm, respectively. Upon full grinding, the λ em, max of Re‐phase is bathochromically shifted to 775 nm. The ground powder of Re‐phase becomes metastable as a consequence of noncovalent conformational locking and that the red to near‐infrared (large colour difference) mechanochromism arises from the high degree of conformational coplanarity. This strategy is both conceptually and synthetically simple and offers a promising approach to the development of organic piezochromic materials with wide‐range redshift and excellent penetrability. Abstract : Noncovalent conformational locks are shown to be an effective strategy to endow the highly coplanar luminophore with good stability and high fluorescence efficiency. The high degree of conformational coplanarity is responsible for red to near‐infrared mechanochromism of metal‐free crystals.